Assessment of ecotoxicological effects of Fojo coal mine waste elutriate in aquatic species (Douro Coalfield, North Portugal) - Narayan, Aracelis; Diogo, Bárbara S.; Mansilha, Catarina; Espinha Marques, Jorge; Flores, Deolinda; Antunes, Sara C. (Frontiers in Toxicology, 2024)
The exploitation of anthracite A in the Pejão mining complex (Douro Coalfield, North Portugal) resulted in the formation of several coal waste piles without proper environmental control. In 2017, a new pedological zonation emerged in the Fojo area, after the ignition and self-burning of some of the coal waste piles, namely: unburned coal waste (UW); burned coal waste, and a cover layer (BW and CL, respectively); uphill soil (US); mixed burned coal waste (MBW); downhill soil (DS). This study aimed to evaluate the toxic effects of 25 soil elutriates from different pedological materials. Allivibrio fischeri bioluminescence inhibition assay, Lemna minor growth inhibition assay, and Daphnia magna acute assay were used to assess the toxicity effects. Additionally, total chlorophyll and malondialdehyde (MDA) content and catalase (CAT) activity were also evaluated in L. minor. The results obtained from each endpoint demonstrated the extremely heterogeneous nature of soil properties, and the species showed different sensibilities to soil elutriates, however, in general, the species showed the same sensitivity trend (A. fischeri > L. minor > D. magna). The potentially toxic elements (PTE) present in the soil elutriates (e.g., Al, Pb, Cd, Ni, Zn) affected significantly the species understudy. All elutriates revealed toxicity for A. fischeri, while US1 and UW5 were the most toxic for L. minor (growth inhibition and significant alterations in CAT activity) and D. magna (100 % mortality). This study highlights the importance of studying soil aqueous phase toxicity since the mobilization and percolation of bioavailable PTE can cause environmental impacts on aquatic ecosystems and biota.